No-visible-scar cholecystectomy - Tadeusz M. Wróblewski; Sebastian Piotrowicz; Marcin Kotulski; Piotr Gierej; Bogna Ziarkiewicz-Wróblewska (Videosurgery and Other Miniinvasive Techniques)
Introduction: Single incision laparoscopic surgery (SILS) is a laparoscopic method providing a good cosmetic effect,but requiring the application of special ports and instruments enabling the surgeon to perform the procedure.We report three-ports cholecystectomy through umbilical and suprapubic incisions performed with typical laparos -copic instruments which calls no-visible-scar cholecystectomy (NVSC).Material and methods: Twenty patients with symptomatic cholelithiasis were qualified for NVSC. Typical CO2 pneumoperitoneumwas done after umbilical skin incision. Two ports of 5 mm were inserted in the maximum externaledges of this incision. After cystic duct and cystic artery dissection the right one was exchanged for a port of 11 mm.The second incision for the 11-mm trocar for the laparoscope was done in the suprapubic median line within the hairarea.Results: Cholecystectomies were performed without any conversion to classical laparoscopic cholecystectomy (LCH)or open surgery. They were not technically identical due to the gradual improvement in the access and manipulationof instruments. The time of the intervention ranged from 2 hours during the introduction of the new method to 50 minfor the last procedures. No postoperative complications were observed and all patients were discharged not later thanafter conventional LCH.Conclusions: NVSC is a three-port laparoscopic intervention performed with typical laparoscopic instruments. It ismore convenient for the surgeon than single incision LCH, because the placement of the optic in the suprapubic regiongives more space for the instruments. It also provides a very good cosmetic effect of the intervention. The describedprocedure is easy to learn and in case of technical problems additional ports can be applied (as in typical LCH).